Effect of three species of host tree on the cold hardiness of overwintering larvae of Anoplophora glabripennis (Coleoptera: Cerambycidae) - Yuqian FENG; Reaxit TURSUN; Zhichun XU; Fang OUYANG; Shixiang ZONG (European Journal of Entomology, 2016)
The Asian long-horned beetle, Anoplophora glabripennis, is a serious destructive pest of forests throughout China as it attacks a wide range of host plants. The effect of host trees on the cold hardiness of A. glabripennis larvae could be the basis for predicting the performance of this forest pest on different common hosts.To evaluate the effect of different species of host plant on the cold hardiness of overwintering larvae of A. glabripennis, we measured the supercooling point (SCP), fresh mass, protein content and concentrations of low molecular weight substances in overwintering larvae collected from three different host species (i.e., Populus opera, Populus tomentosa and Salix matsudana). Mean SCPs and protein contents of larvae from these three hosts differed significantly. The SCPs and protein contents of the larvae collected from P. opera and P. tomentosa were significantly higher than those collected from S. matsudana. The concentrations of glycerol, glucose and trehalose in overwintering larvae collected from these host species also differed significantly, but there were no significant differences in the concentrations of sorbitol and inositol. The larvae that were collected from S. matsudana had the highest concentrations of glycerol and trehalose and those from P. opera the lowest contents of glycerol, whereas those from P. tomentosa had the lowest concentrations of trehalose but the highest concentrations of glucose. Because of the significant differences in the quantities of these biochemical substances in their bodies, the cold hardiness of overwintering larvae of A. glabripennis was significantly dependent on the tree they fed on. These effects on the cold hardiness of the overwintering larvae might affect the selection of a host tree and therefore the spread of this beetle.